Efektivitas Aromaterapi Kulit Jeruk Lemon dalam Penanganan Mual dan Muntah Pada Ibu Hamil Trimester I di Wilayah Kerja UPT Puskesmas Panca Makmur - Syahriah Syahriah; Lailatul Mustagfiroh (Universitas Malahayati Lampung, 2024)
ABSTRACT In Indonesia, almost 50-90% of pregnant women experience nausea in the first trimester. If complaints of nausea, vomiting continues for a long time, it can result in reduced nutritional intake needed. One of the non -pharmacological therapy to reduce nausea and vomiting is by aromatherapy lemon lemon peel. Aromatherapy Lemon orange peel is useful to stabilize the central nervous system, cause feelings of pleasure to increase appetite, improve blood circulation, and as a sedative of this study was to determine the effectiveness of lemon aromatherapy in handling nausea and vomiting in trimester 1 pregnant women in the area of the Pancamakmur Puskesmas UPT. The population in this study are all trimester I pregnant women who experience nausea and vomiting with purposive sampling sampling. Types of primary data in the form of demographic data and nausea and vomiting frequency results of interviews with pregnant women and secondary data in the form of the number of pregnant women sourced from the local village midwife. Univariate analysis based on the characteristics of respondents using SPSS applications and Bivariate analysis with McNemar statistical tests using the SPSS. Frequency of nausea before being given a majority lemon skin aromatherapy with a medium category as many as 16 pregnant women (88.9%) and vomiting majority with a medium category of 14 Pregnant women (77.8%). After being given aromatherapy lemon peel, the majority nausea frequency with a mild category of 12 pregnant women (66.7) The frequency of the majority vomiting with a mild category of 15 pregnant women (83.3%). The results of the analysis of the nonparametric test mcnembar obtained the value of ρ = 0.002 α 0.05. From the results of the analysis it was concluded